(untitled) (Third Sector Social Economic Review, 2019)
The minimum wage, which is the income of the trapped labor between the production gears, and the increases made thereon, are evaluated by some by cost and inflation effect, some by distribution, production increase and contribution to growth. At this point, revealing the effects of minimum wage on inflation and employment will provide an illuminating contribution to the subject. In this study, the relationship between the minimum wage increase and inflation and unemployment was analyzed with VECM method using the six-month data for the periods of 1988: SI - 2018: S1. In the study, the following main conclusions are reached: In the short term, 31% of the change in CPI (Consumer Price Indeks) stemmed from the minimum wage increase and in the long term this rate is 43%. Similarly, in the short-term, the rate of change in CPI stems from the unemployment rate of 1.5%, which is up to 3.2% in the long run. It is observed that the effects of the minimum wage growth rate and the unemployment rate on the CPI increased as the short-term period goes on. In two of these three variables, that is, there is a stronger interaction between the rate of minimum wage growth and inflation as long term; between minimum wage and unemployment in the short term as fluctuating and decreasing as long term is reached.